2018
DOI: 10.1111/apa.14386
|View full text |Cite
|
Sign up to set email alerts
|

Neonatologists can impede or support parents’ participation in decision‐making during medical rounds in neonatal intensive care units

Abstract: The neonatologists played a central role in facilitating parental participation and their interaction during medical rounds were characterised by the level of parent participation in decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…This, in turn, facilitates parents' participation in caregiving at their own pace, and promotes their empowerment and autonomy, resulting in parents experiencing acknowledgement of their personal situation (Brødsgaard et al, ; Fegran et al, ). This is fundamental for realising shared decision‐making between parents and healthcare professionals (Axelin, Outinen, Lainema, Lehtonen, & Franck, ; Hoffmann, Montori, & Del Mar, ). It is important, however, that collaboration and care plans are documented to guide different nurses in their daily work with the family, creating consistency and supporting parent trust.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, in turn, facilitates parents' participation in caregiving at their own pace, and promotes their empowerment and autonomy, resulting in parents experiencing acknowledgement of their personal situation (Brødsgaard et al, ; Fegran et al, ). This is fundamental for realising shared decision‐making between parents and healthcare professionals (Axelin, Outinen, Lainema, Lehtonen, & Franck, ; Hoffmann, Montori, & Del Mar, ). It is important, however, that collaboration and care plans are documented to guide different nurses in their daily work with the family, creating consistency and supporting parent trust.…”
Section: Discussionmentioning
confidence: 99%
“…Communication that integrates parents' personal values and preferences is central to reach a shared understanding and decision‐making (Axelin et al, ; Weis, Zoffmann, & Egerod, ). Nurses may think they know what the parents want to say (Weis et al, ), but studies have shown discrepancies between the support provided by the nurses and the parents' actual perceptions and needs (Fegran et al, ; Franck & Axelin, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians can support parental participation in decision making during medical rounds by asking the parents how they view their child's condition. The parents are able to express how their child is doing, and the neonatologist can express agreement and understanding both verbally and through non-verbal communication such as nodding and smiling (Axelin, Outinen, Lainema, Lehtonen, & Franck, 2018). One study showed that parents who were allowed to participate in the medical round, and were given the opportunity to take decisions concerning their child, felt that they were closer to their child (Treherne, Feeley, Charbonneau, & Axelin, 2017).…”
Section: Main Interpretation and Discussionmentioning
confidence: 99%
“…Axelin et al. observed the parents of 11 singletons and four sets of twins and how they interacted with two neonatologists during 15 medical rounds in a neonatal intensive care unit in Turku, Finland. They found that neonatologists played a central role in facilitating the level of parental participation and that their interaction affected how the parents participated in decision‐making in both positive and negative ways.…”
Section: Communication Between Neonatologists and Parents Affects Decmentioning
confidence: 99%